Effect of Educational Intervention on Knowledge Regarding HIV/AIDS among Nursing Assistant Students of Shree Birendra Hospital, Nepal - Rai, Padma; Adhikari, Anita; Bajracharya, Manjari (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: HIV/AIDS is a serious health problem all across the world. The modes of HIV transmission are unprotected sex with infected individual, injection or transfusion of HIV infected blood or blood products, donations of infected semen, organ transplants taken from an infected person and sharing of unsterilized injection equipment. The alarmingly increasing rate of prevalence of HIV among the youths due to engagement in high risk behaviors show that there is a desperate need for assessments to be conducted to ascertain the existing knowledge, attitudes and sexual practices of youths. Methods: One group pre and post-test experimental research design was adopted for the study. The pretest study was conducted on 4 December, 2012; followed by post- test study after two weeks. The study group was provided with course on HIV/AIDS between the tests. The study was carried out in 121 students of nursing assistants of Shree Birendra Hospital. Results: The findings show that the level of knowledge after educational intervention increases significantly. Conclusion: Educational intervention is likely to be significant in increasing awareness about HIV/AIDS.